ТИЛ ВА МЕНТАЛИТЕТ ТУШУНЧАЛАРИ МУШОҲАДАСИ - Казаков, И.Р. (SCIENCE and SOCIETY, 2023)
In this article, the concepts of language and mentality are interpreted, their constant companionship is shown, and the reflections are summarized of the imaginations specific to the mentality of the Uzbek and Karakalpak peoples in the language.